Chloroplasts with clefts and holes: a reassessment of the chloroplast shape using 3D FE-SEM cellular reconstruction of two species of Chlamydomonas: Chloroplasts with clefts and holes: a reassessment of the chloroplast shape using 3D FE-SEM cellular reconstruction of two species of Chlamydomonas: N. Sato et al - Sato, Naoki; Sato, Mayuko; Wakazaki, Mayumi; Moriyama, Takashi; Hirashima, Takashi; Toyooka, Kiminori (Protoplasma, 2025)
Chloroplasts are usually considered spheroid organelles, but this is not the only shape of chloroplasts. The chloroplast of Chlamydomonas has been typically described as cup-shaped. However, in old studies, it was also modeled as a complex shape with "perforations" or windows. Here, we reconstructed the cellular architecture of Chlamydomonas reinhardtii and C. applanata using an array tomography system installed on a field emission scanning electron microscope. C. reinhardtii chloroplasts resembled a baseball glove or a cup without a side, featuring numerous large and small holes that may facilitate the transport of metabolites and proteins produced in the Golgi apparatus fitted in the holes. In a lipid-accumulating, high-light condition, the chloroplast volume increased by filling the side cleft with an entire wall. Many accumulated large lipid droplets were accommodated within the chloroplast holes, which could have been considered as "chloroplast lipid droplets." Mitochondrial meshworks surrounded the chloroplast. C. applanata chloroplasts appeared like a folded starfish or a cup with many side clefts and a few holes. There was a single mitochondrion or two that branched in a complex form. Tight contacts of various organelles were also found in C. applanata. These reconstructions illustrate the complexity of chloroplast shape, which necessitates a revised understanding of the localization of lipid droplets and the evolution of chloroplasts: The prevailing image of the spheroid chloroplasts that reminds us of the similarity between chloroplasts and cyanobacteria is no longer tenable.